REPRESENTATION OF THE LIFE OF PATRIARCHY IN THE FILM YUNI (CRITICAL DISCOURSE ANALYSIS) - Adinda Maharani (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
The patriarchal culture is very closely related to the existing social order in Indonesia, where many women support it in the domestic sphere so that it is attached to the existence of gender discrimination. One of the films by Kamila Andini with the title “Yuni” represents the social problems experienced by women who are trapped in the conception of patriarchal culture. This study aims to describe and analyze the message of patriarchy and gender discrimination experienced by women in the film Yuni using Sara Mills' critical analysis approach. The results show that there are two concepts of critical discourse analysis, which are seen from the position of the subject and the position of the reader or audience, where this study finds how women are represented as parties who do not have a major role in determining their right to life. The traditional patriarchal culture in Yuni's film scene makes women shackled to a stigma that leads to gender discrimination